Índices de referência para apoio na precificação da cama de aviário como fertilizante - Metzner, Cláudio Marcos (2014)
Data indicate that Brazil imports on average 75% of the nutrients that make up the base of mineral fertilizers. This implies that there is a moderate correlation in prices of mineral fertilizers with the Dollar. Also, it appears that Brazil is the fourth-largest producer of broilers, demonstrating that there is a large volume of waste generation in this activity, which could be used as corn fertilizer and the farmer can sell the bed of avian. Thereby we seek to answer the research questions: How to determine the price of poultry litter from their nutrients? And how to determine which is the best option in economic terms, of fertilization with avian or mineral bed, to the farmer who plans corn? Thus, the aim of this research was to establish benchmarks for pricing support in the aviary as fertilizer bed. The results show that there is a moderate correlation between the prices of poultry litter, corn and the dollar and the selling price of the poultry litter, from its fertilizer value oscillates between US $ 85 and $ 140 to tonne and that from the productivity of organic fertilization x mineral, it was elaborated arate of reference a benchmark, demonstrating that for the organic fertilizer, poultry litter, is the best option for the farmer who plans corn, in financial terms, considering prices and productivity, the market price in the poultry litter should be over 15% of the price of mineral fertilizer, with formulation 8-20-20